Spontaneous pneumothorax caused by an inflammatory myofibroblastic tumor-like lesion in a 14-year-old girl: a case report - Hisayuki Miyagi; Daisuke Ishii; Masatoshi Hirasawa; Shunsuke Yasuda; Naohisa Toriumi; Takeo Sarashina; Mishie Tanino; Mio Tanaka; Yukichi Tanaka; Kazutoshi Miyamoto (Surgical Case Reports, 2020)
Abstract Background Spontaneous pneumothorax occurs more often in younger, slim, and shallow-chested men. Although less common, differential diagnoses for secondary pneumothorax in children are asthma, emphysematous blebs, catamenial pneumothorax, and others. We report a patient who presented with pneumothorax and was found to have an inflammatory myofibroblastic tumor (IMT)-like lesion, and present a review of the related literature. Case presentation A 14-year-old girl visited her physician for chest pain that developed while exercising. Although chest drainage was performed, the symptoms associated with a collapsed lung did not improve, and she was referred to our hospital. Computed tomography revealed the presence of a 19 × 17-mm cyst with a thick wall in the apex of the right lung. She was tested for infectious diseases, namely tuberculosis, but the results were not definitive. Catamenial pneumothorax was also suspected because she was menstruating when she presented to our hospital. As a therapeutic diagnosis, we performed a thoracoscopic partial resection of the right upper lobe of the lung. Three small openings were identified inside the cyst, suggesting connection with the bronchiole. The lesion was pathologically diagnosed as an IMT-like lesion. Considering the progress so far, we considered that the final diagnosis to be an IMT. The patient was discharged on postoperative day 3, and we have followed her for the past 6 months with no local recurrence or metastasis. Conclusions IMT is not uncommon in children. Therefore, this lesion should be considered as a possible diagnosis if children and young adults develop spontaneous pneumothorax.